Design of a half-bridge inverter with digital SPWM control for pure sine wave output - Akaaboune, Jalil; Mourabit, Bouazza El; Oulaaross, Mohamed; Benchagra, Mohamed (International Journal of Applied Power Engineering (IJAPE), 2025)
To foster the widespread adoption of solar power, especially that produced by photovoltaic (PV) systems, we must move beyond the mere utilization of renewable energy sources. Prioritizing cost-effective approaches through innovative grid integration is essential. This strategic transformation significantly contributes to the global expansion of electrical energy production. One pioneering approach involves the implementation of inverters operating at high frequencies to efficiently filter and eliminate undesirable current harmonics, thus enhancing system performance. This innovative technique relies on the generation of rapid complementary digital pulse width modulation (PWM) signals, complete with built-in dead time, to manage a half-bridge inverter with a single phase. The paper recommends employing the IR2110 driver, an often-used component for MOSFET switch management, to execute this strategy. The entire system is controlled by high-frequency PWM signals, meticulously programmed for precision, generated by a microcontroller driver board. With its adaptability to various renewable energy conversion devices, this methodology extends its utility beyond solar energy. Practical tests have confirmed the efficacy of this strategy. Future research in this field should scrutinize the effect of PWM on system stability and harmonic distortion, explore advanced modulation methods, align PWM approaches with upcoming power electronics technologies, and work towards improving system efficiency.